2020
DOI: 10.1116/1.5140841
|View full text |Cite
|
Sign up to set email alerts
|

Plasma deposition—Impact of ions in plasma enhanced chemical vapor deposition, plasma enhanced atomic layer deposition, and applications to area selective deposition

Abstract: In this paper, the emerging role of ionic species in plasma assisted chemical deposition processes is discussed in details for commemorating the Career of John Coburn who studied the role of ionic species in plasma etching processes forty years ago. It is shown that in both Plasma Enhanced Chemical Vapor Deposition (PECVD) and Plasma Enhanced Atomic Layer Deposition (PEALD) processes, plasma ions can play a major role in tuning a wide range of physical properties of thin films. In both processes, the possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 85 publications
0
27
0
2
Order By: Relevance
“…Finally, the difference in WER with and without ion exposure can be exploited for topographic selective processing on 3D substrates. 12,14 This work thus provides valuable insights for tailoring SiO2 film growth by ALD in state-of-the-art and nextgeneration device applications.…”
Section: Please Cite This Article As Doi: 101063/50015379mentioning
confidence: 96%
See 1 more Smart Citation
“…Finally, the difference in WER with and without ion exposure can be exploited for topographic selective processing on 3D substrates. 12,14 This work thus provides valuable insights for tailoring SiO2 film growth by ALD in state-of-the-art and nextgeneration device applications.…”
Section: Please Cite This Article As Doi: 101063/50015379mentioning
confidence: 96%
“…10,11 As shown for several plasma ALD processes, energetic ions impinging on the surface during the plasma steps can play an important role. 12 For example, Profijt et al 13 demonstrated that significantly increasing the kinetic energy of the ions through substrate biasing can induce a change in the growth per cycle (GPC)…”
mentioning
confidence: 99%
“…Attempts have been made to lower the temperature for ASD in CVD by redesigning precursors than can be used at lower temperatures without changing the selectivity process [104]. An alternative for thermal CVD is PECVD where ASD can be applied at lower temperatures (< 400 °C) [105][106][107]. Moreover, since ALD usually operates at lower temperatures than CVD and the precursors are separately delivered during deposition, ALD is an excellent approach for ASD, where the growth on certain areas of the substrate can be controlled by modifying the surface chemistry, hence allowing for more flexibility in the processing [85].…”
Section: Area Selective Cvdmentioning
confidence: 99%
“…The presence of specific ions created in plasma in the PECVD technique promotes precursor dissociation at the surface and thus makes deposition possible at a lower temperature compared to conventional deposition techniques [78]. Since PECVD was introduced, much research has been dedicated to understanding the role of plasma-reactive species in TiO 2 film growth [12].…”
Section: Plasma-enhanced Chemical Vapor Depositionmentioning
confidence: 99%
“…For example, a process of plasma-enhanced/assisted chemical vapor deposition (PECVD/PACVD; here we will use the PECVD term hereafter) at atmospheric pressure can be optimized by using a mixture of various gases as well as a gas/liquid precursor in the feed gas to enhance plasma chemistry [8]. The scientific and industrial communities recognize the advantage of using APP already because of rich plasma chemistry, which plays a significant role in material processing techniques, such as PECVD, plasma-assisted etching, and plasma polymerization [1,[9][10][11][12]. Plasma can effectively deliver reactive chemical species that promote surface reactions that would otherwise require a high substrate temperature.…”
Section: Introductionmentioning
confidence: 99%